ANALYSIS OF CHARACTER EDUCATION VALUES IN THE FILM KAKA BOSS BY ARIE KRITING: Analisis Nilai-Nilai Pendidikan Karakter dalam Film Kaka Boss Karya Arie Kriting - Ahada Wahyusari; Siti Habibah; Abdul Malik; Dody Irawan; Fabio Testy Arience Loren; Jeni Periyani (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to analyze the values of character education portrayed in the film Kaka Boss by Arie Kriting. This study uses a descriptive qualitative approach with content analysis techniques. The object of this research is the entire storyline and dialogue of the film Kaka Boss, which was released in 2023. The data were collected through documentation and note-taking techniques and analyzed using Miles and Huberman’s model involving data reduction, data display, and conclusion drawing. The results reveal several dominant character education values, including (1) responsibility, as shown through the character of Kaka who protects and guides children in difficult environments; (2) discipline, demonstrated through consistent efforts to instill good behavior; (3) caring and empathy, illustrated by emotional support given to others; (4) cooperation and social awareness, as the characters work together to solve problems; and (5) honesty and courage, shown in scenes where characters choose the right path despite personal risks. These values reflect the core principles of character education aligned with the Indonesian national education goals and highlight the potential of film as a medium for character development.